Hubungan Intensitas Komunikasi Interpersonal Antara Orang Tua dan Anak dengan Kenakalan Anak : (Studi Kasus Siswa SMA Negeri 6 Kota Bengkulu) - Bariq Rizky Abdillah; Moh. Amin Tohari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The intensity of interpersonal communication between parents and children involves actions and interactions that influence children’s behavior. This study aims to identify the forms of juvenile delinquency and the intensity of interpersonal communication between parents and children. The main issues in communication include aspects of openness, empathy, support, positive attitudes, and equality. The study employs a qualitative approach with a descriptive method, purposive sampling technique, and data collection through interviews, observations, and documentation. Data analysis is conducted through the stages of data collection, reduction, presentation, and conclusion drawing using triangulation. The results show that a lack of open communication between children and parents, insufficient empathy, lack of support, and inadequate positive attitudes and equality in communication can trigger juvenile delinquency. Additionally, internal family conflicts act as barriers to communication, leading to tension and causing children to withdraw and avoid interaction with their parents.